1999
DOI: 10.1021/bi9904454
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Nonbridged Coordination of p-Nitrophenyl Phosphate to the Dinuclear Fe(III)−M(II) Center in Bovine Spleen Purple Acid Phosphatase during Enzymatic Turnover

Abstract: The pH dependence of the catalytic parameters k(cat) and K(M) has been determined for the Fe(III)Fe(II)- and Fe(III)Zn(II)-forms of bovine spleen purple acid phosphatase (BSPAP). The parameter k(cat) was found to be maximal at pH 6.3, and a pK(a) of 5.4-5.5 was obtained for the acidic limb of the k(cat) vs pH profile. Two different EPR spectra were detected for the phosphate complex of the mixed-valent diiron enzyme; their relative amounts depended on the pH, with an apparent pK(a) of 6. The EPR spectra of Fe(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 44 publications
8
82
0
Order By: Relevance
“…In agreement with previous studies [40,[45][46][47] pK es2 is assigned to a conserved histidine residue in the second coordination sphere, which is likely to act as a proton donor to the leaving alcohol group during catalysis [14,[47][48][49]. Site-directed mutagenesis studies identified His92 as the likely residue [47].…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufsupporting
confidence: 89%
“…In agreement with previous studies [40,[45][46][47] pK es2 is assigned to a conserved histidine residue in the second coordination sphere, which is likely to act as a proton donor to the leaving alcohol group during catalysis [14,[47][48][49]. Site-directed mutagenesis studies identified His92 as the likely residue [47].…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufsupporting
confidence: 89%
“…The presence of a bridging l-hydroxo group in the active purple acid phosphatases from pig, bovine, and red kidney bean is supported by saturation magnetization measurements, which indicated weak exchange coupling [33,34]. A role as the attacking nucleophile has been attributed to this bridging group as an alternative to the hydroxo group coordinated to ferric ion [35][36][37][38]. The pK a of $2 could alternatively be due to the first ionization of the substrate, although we would expect the value to be lower-the first acid dissociation of phenyl phosphate is reported to be 0.3 [25].…”
Section: Resultsmentioning
confidence: 98%
“…For both enzymes the K m values for the substrate p-NPP increase as the pH is increased, an observation which is likely to be due to the deprotonation of a histidine residue in the substrate binding pocket of the enzyme. 16,39 The inhibitory effect of vanadate on the activity of red kidney bean PAP was determined at optimum pH (pH 6.2). At that pH vanadate monomers tend to oligomerise in solution provided the total concentration of the tetraoxo anion is ≥ 0.25 mmol L -1 .…”
Section: Resultsmentioning
confidence: 99%
“…For both enzymes the K m values for the substrate p-NPP increase as the pH is increased, an observation which is likely to be due to the deprotonation of a histidine residue in the substrate binding pocket of the enzyme. 16,39 Vol. 17, No.…”
mentioning
confidence: 99%